Comparison of Psychological Problem Areas in Diabetes between Diabetic Elderly Residents of Kahrizak Nursing Home With Living in Homes, In Tehran - Homa Nasseh; Roya Ghasemzade; Mohammad Kamali; Abass Rahimi Foroushani; Seyed Masoud Arzaghi; Ali Asghar Arastoo (University of Social Welfare & Rehabilitation Sciences, 2014)
Objectives: Due to increased growth rates of diabetes and aging in the country subject of this research was a comparison of problem areas in diabetes among diabetic elderly residents of the Nursing Home with living in the home. Methods & Materials: This study is a descriptive-analytical research and among diabetic elderly nursing home residents and elderly living at home in Tehran Who 93 persons from each group were randomly selected. PAID questionnaire used for this study (α=0.94), (validity=0.88) and statistical analysis T test, Kolmograph and Anova was performed with SPSS 16 software. Results: The testing shows a significant difference in Psychological distress in relation to diabetes management and depression-related domains. Nursing home residents in these two areas show better results (P<0.01). Both groups show better scores in men. Conclusion: Increasing the quality of life in diabetic elder people, need to indicate medical aspects and other aspects that associated with the disease. For example improving the emotional status in nursing home residents and caring in home residents, is important.